Implementasi Teknologi Augmented Reality dengan Visual Tracking Untuk Pengenalan dan Promosi UMKM di Kota Kupang - Adriana Z. Laurha Sadi; Dewi Anggraini; Yohanis Malelak (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
The development of digital technology encourages Micro, Small, and Medium Enterprises (MSME) to adapt to more innovative and interactive promotional methods. In Kupang City, most UMKM still rely on traditional promotions, resulting in limited marketing reach and less ability to attract maximum consumer attention. This study aims to design and implement a visual tracking-based Augmented Reality (AR) application as a medium for introducing and promoting UMKM  products. The method used is Research and Development (R&D) with a Waterfall software development model, which includes the stages of needs analysis, design, implementation, testing, and maintenance. The application was developed using ZapWorks Studio for the visual tracking feature and Blender for creating 3D objects. Test results using a user evaluation approach show that the application is able to detect markers well and display product information interactively through 3D objects. Respondents from UMKM and general users stated that this application is easy to use, the AR display is attractive, and it is effective in increasing the attractiveness of product promotions. Thus, Augmented Reality technology is proven to be feasible and has the potential to become an innovative digital promotional medium for UMKM in Kupang City.